Analogical Evaluation of Endoscopic Septoplasty in Posterior Septal Deviation - Hasnain Haider, Bakht Aziz, Umair Wahab, Atiq U Rehman, Zahra Aleem, Maryam Umar, Irshad Malik, Kashif Iqbal Malik (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Deviated Nasal Septum is one of the pronounced causes of Nasal Obstruction. A number of surgeries are being done since decades to alleviate symptoms. Recent advancement with endoscopes has revolutionized the surgical approach towards minimal invasive procedures. Aim: To analyze the post-op hospital stay and complications in headlight vs. endoscopic septoplasty Study design: The study is Cross sectional Randomized Control Trial. Place and duration of study: We conducted this study in ENT Unit I of Jinnah Hospital Lahore from June 2021 to January 2022. The follow up time was 2 months. Methodology: We performed this study on 30 patients who were diagnosed with Posterior Septal deviation. We randomly divided the patients into two groups. Group A was to undergo trans-nasal trans-speculum (TNTS) septoplasty while group B, endoscopic septoplasty. We analyzed the outcomes in the form of incidence of anterior nasal packing, post-op hospital stays and rate of adhesion formation. Results: We concluded that in Group A, nasal packing was required in 14(93.3%) patients, adhesion formation in 2(13.3%) patients and the mean post-operative hospital stay was 2.13±0.352 days while in Group B, only 3(20%) patients needed anterior nasal packing, none developed post-surgical adhesion formation and the mean postop hospital stay was 1.00±0.000 days. Practical implication: This study delineated that endoscopic septoplasty once mastered is far superior to Endonasal Conventional septoplasty and must be adopted in all public and private sectors to improve cost-effectiveness. Conclusion: We concluded that endoscopic septoplasty is far superior to trans-nasal trans-speculum (TNTS) septoplasty when post-op hospital stays and incidence of nasal packing was concerned in posterior septoplasty. However, there was no statistical difference in terms of post-surgical adhesion formation among the two studied groups. Keywords: Endoscopic Septoplasty, Trans-nasal trans-speculum (TNTS) septoplasty, Deviated Nasal Septum